Analysis of Drug Management Ability on the Elderly in the East Surabaya Using MedMaIDEâ„¢ - Rakhmania Salam, Anisa; rakhma, Aulia Nur Shabrina; Belinda Nabilah Ekapratista; Eunike Natasya Panjaitan; I Putu Bagus Pradnyanantha; Nabila Nur Haliza; Ragil Putri Pramesti; Shefilla Mangestiti Berliana; Swastika Bintang Prameysti; Yossy Prastyo; Gusti Noorrizka Veronika Ahmad (Jurnal Farmasi Komunitas, 2023)
The elderly are at the highest risk for drug-related problems caused by age-related physiological changes, multiple chronic illnesses, polypharmacy, and poor drug management.  This study aims  to analyze the ability of elderly regarding drug management. This study used an observational research method with an elderly population in the East Surabaya area. The research instrument used was MedMaIDETM (Medication Management Instrument for Deficiencies in the Elderly), which can be used to measure ability in medication management in the elderly community who are undergoing self-medication with at least one medication.  Sampling was carried out  using  a non-random sampling method with a purposive sampling technique. The number of respondents obtained in this study were 100 elderly who live in the East Surabaya area. The inclusion criteria for research respondents were: (1) willing to be a respondent; (2) domiciled in the East Surabaya area; (3)  aged â‰¥ 60 years; (4) able to communicate in Indonesian; and (5) consuming at least one medicine. The variable studied was drug management skills in the elderly which includes knowledge of the medications aspect, knowledge on how to take the medication aspect, and knowledge on how to obtain the medication. The average MedMAIDE scores of respondents in the three domains with a total average value of 1.18 and a standard deviation of 0.10, meanings each elderly at least had one deficiency out of 13 maximun score of deficiencies. There were 70 respondents out of 100 respondents who had limitations in drug management with one deficiency score as the smallest score and the largest total deficiency score being 7. Meanwhile, 30 other respondents had a no deficiency. The most difficult tasks were identified the problems after taking the medication, fill a glass with water, sip enough water to swallow medication and identify if a refill exists on a prescription. The ability of elderly people in the East Surabaya area to manage their medicines was good. The elderly were able to recognize the drugs used, use the drugs correctly, and comply with drug administration.